Variations of biochemical and hematic parameters following Taoist qigong practice - Manzaneque-Vázquez, Juan Manuel; Vera-Fernández, Francisca María; Rodriguez, FM; Vadillo, Miguel; Bendayan, Rebecca; Blanca-Mena, María José; Heiniger, AI (My University, 2014)
Qigong is an ancient Chinese psychosomatic discipline which employs specially designed body movements to achieve mind-body integration, preserve health, and pursue longevity. The Taoist school of qigong, one of the main traditions within this Chinese discipline, has a particular approach that emphasizes naturalness for the achievement of those goals. Albeit diverse methods of qigong have already been shown to display significant psychobiological effects, Taoist qigong has been scarcely investigated to date. Thus, this research was carried out with the aim of shedding light on the effects of Taoist qigong on biochemical and hematic parameters measured shortly after practice. Forty five naive subjects participated in the study, twenty-eight in the experimental group and the rest in the control group. Experimental subjects underwent a qigong training program consisting of three half-hour guided sessions per week, for the period of one month. Blood samples for the quantification of biochemical and hematic parameters were drawn from all subjects the day before the experiment commenced and one hour after the last session of practice concluded. Analysis of covariance (ANCOVA) was performed as statistical analyses. Our results showed that after completing the qigong program, experimental subjects displayed lower levels of serum albumin, as well as lower values of Mean Corpuscular Hemoglobin (MCH) and Mean Corpuscular Hemoglobin Concentration (MCHC), when compared to control. These findings, therefore, reveal that the practice of Taoist qigong for a short period of one month exerted a peculiar biochemical and hematimetric influence, which suggests interesting psychobiological and clinical implications.
Keywords: Medicinas alternativas; Taoist qigong; Biochemical; Hematic; Parameters